Proposition d’un outil d’aide au diagnostic du syndrome du canal carpien pour les acteurs de la santé au travail - Florence Bazzaro; Jean-Claude Sagot (Perspectives Interdisciplinaires sur le Travail et la Santé)
People involved with occupational health at work are faced with a lack of quantitative tools to monitor and diagnose Carpal Tunnel Syndrome (CTS). In order to fill this gap, we developed a device for rapid CTS diagnosis which is composed of two complementary quantitative tests: the wheel test, which consists in detecting notches on a rotating wheel, and the beam test, which consists in detecting various forces exerted on a finger. We conducted two experimental studies to validate this device. The first one demonstrated the repeatability of the measures. The second one studied the sensitivity and specificity of our tool as compared to an electro-diagnosis test. The results show that our CTS detection device has excellent discriminatory power that allows practitioners to differentiate between healthy and CTS-affected subjects.